2021
DOI: 10.3389/fpsyg.2021.750904
|View full text |Cite
|
Sign up to set email alerts
|

Linking Positive Psychology and Intercultural Competence by Movies: Evidence From Brunei and Romania

Abstract: Cultural consumption provides numerous benefits for individuals, especially for younger generations. Imaginary travel narratives can shape people’s perceptions about other cultures thus are useful tools for developing intercultural competences. On the other hand, positive psychology provides an approach to understand different aspects of students/youngsters’ wellbeing. This study investigates the wellbeing associated with learning the meanings of being different and growing in emotional resilience, flexibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 70 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…It has been proven by a number of experiments that the PERMA-Pro ler he proposed has acceptable model t and consistency both internal and cross-temporal. More speci cally, the scale has been widely used to measure the subjective well-being of adolescents and college students [15].…”
Section: The De Nition and Evaluation Of Subjective Well-beingmentioning
confidence: 99%
“…It has been proven by a number of experiments that the PERMA-Pro ler he proposed has acceptable model t and consistency both internal and cross-temporal. More speci cally, the scale has been widely used to measure the subjective well-being of adolescents and college students [15].…”
Section: The De Nition and Evaluation Of Subjective Well-beingmentioning
confidence: 99%
“…Psychological research has also demonstrated that conceptions of "happiness" and "psychological well-being" differ across cultures and change over time [18], making it useful for the purposes of scientific investigation to identify more specific elements of "happiness" or "psychological well-being" rather than treating "happiness" or "psychological well-being" as a singular, invariant, and holistic property [16]. The PERMA framework that Seligman [16] proposed has been incredibly influential in contemporary research on psychological well-being and has been validated and applied in psychological studies of well-being in participants across cultures and in different countries including Australia [19], Brunei [20], Canada [21], China [22], Germany [23], Greece [24], Hong Kong [25], India [26], Italy [27], Japan [28], Qatar [29], Romania [20], South Korea [30], Turkey [31], and the United Arab Emirates [32].…”
Section: Muay Thai and Psychological Well-beingmentioning
confidence: 99%
“…Interestingly enough, recent research from scholarly dissertations and professional publications in education and sociology suggest that Muay Thai training can in fact contribute to positive emotions. For example, Dimson et al [40] studied young Muay Thai athletes (n = 10, age range [16][17][18][19][20][21][22][23] and found that Muay Thai training helped to improve their self-esteem and emotional regulation. In another empirical study, Phipps [41] conducted interviews with female Muay Thai athletes (n = 14) and found that most of them experienced pleasurable excitement while training and competing.…”
Section: Muay Thai and Psychological Well-beingmentioning
confidence: 99%